Measurement report: Brown carbon aerosol in rural Germany - sources, chemistry, and diurnal variations - Jiang, Feng; Saathoff, Harald; Ezenobi, Uzoamaka; Song, Junwei; Zhang, Hengheng; Gao, Linyu; Leisner, Thomas (Atmospheric chemistry and physics, 2025)
Brown carbon aerosol (BrC) is a major contributor to atmospheric air pollution in Europe, especially in winter. Therefore, we studied the chemical composition, diurnal variation, and sources of BrC from 17 February to 16 March 2021 at a rural location in southwest Germany. In total, 178 potential BrC molecules (including 7 nitro aromatic compounds, NACs) were identified in the particle phase comprising on average 83 ± 44 ng m−3, and 31 potential BrC (including 4 NACs) molecules were identified in the gas phase contributing on average 8.5 ± 6.7 ng m−3 during the whole campaign. The average light absorption of seven NACs in the particle phase was 0.2 ± 0.2 Mm−1, contributing to 2.2 ± 2.1 % of total BrC absorption at 370 nm. In addition, diurnal variations show that gas-phase BrC was higher in the daytime and lower at night. It was mainly controlled by secondary formation (e.g. photooxidation) and particle-to-gas partitioning. Correspondingly, the particle-phase BrC was lower in the daytime and higher at night. Secondary formation dominates the particle-phase BrC with 61 ± 21 %, while 39 ± 21 % originated from biomass burning. Furthermore, the particle-phase BrC showed decreasing light absorption due to photochemical ageing. This study extends the current understanding of real-time behaviours of brown carbon aerosol in the gas and particle phase at a location characteristic of central Europe.
Gesehen am 28.07.2025